Social representations of living with HIV/AIDS and experiences of prejudice in Brazil - Giacomozzi, Andréia Isabel (2019)
Objective: This study aimed to investigate the social representations of people living with HIV/AIDS and their experiences of prejudice. Method: One hundred fifty- four (154) people living with HIV/AIDS participated in the study. Data were collected through semi-structured interviews and underwent a descending hierarchical analysis through the IRaMuTeQ software. Results: The study results showed that for these individuals the moment of diagnosis was perceived as a turning point, but after a while they eventually anchored their health condition as a chronic disease. Infection occurred mostly due to intravenous drug use and unprotected sex. Discussion: The participants reported that dealing with social prejudice was more difficult than living with HIV/ AIDS. Prejudice was a recurring daily experience for those who decided to reveal their serological status, and led to a practice of concealing their condition from society to avoid being rejected.